2005
DOI: 10.1037/0735-7044.119.2.548
|View full text |Cite
|
Sign up to set email alerts
|

NMDA Antagonist MK-801 Does Not Interfere With the Use of Spatial Representation in a Familiar Environment.

Abstract: There is disagreement among researchers concerning whether glutamatergic N-methyl-D-aspartate (NMDA) receptors play a role in constructing spatial representations. Therefore, the authors reexamined the effects of the NMDA antagonist on a spatial discrimination task using rats in a water pool. The authors confirmed that MK-801 impaired acquisition of the spatial discrimination task (Experiment 1). When rats were pretrained before drug treatment, MK-801 induced learning deficits in the novel environment but not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
1
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 26 publications
3
10
1
2
Order By: Relevance
“…As in the case of place cells, the directional signal carried by the HD system also shows consolidation in new environments (Dudchenko and Zinyuk, 2005) and so it would be interesting to determine if this plasticity can be altered by NMDA antagonists. The finding that spatial learning is most impaired by NMDA blockade when the training occurs in an unfamiliar environment (Caramanos & Shapiro, 1994; Uekita & Okaichi, 2005) is consistent with the possibility that the acquisition of a spatial task is dependent on the consolidation of the environment into the neural circuitry supporting spatial behavior.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…As in the case of place cells, the directional signal carried by the HD system also shows consolidation in new environments (Dudchenko and Zinyuk, 2005) and so it would be interesting to determine if this plasticity can be altered by NMDA antagonists. The finding that spatial learning is most impaired by NMDA blockade when the training occurs in an unfamiliar environment (Caramanos & Shapiro, 1994; Uekita & Okaichi, 2005) is consistent with the possibility that the acquisition of a spatial task is dependent on the consolidation of the environment into the neural circuitry supporting spatial behavior.…”
Section: Discussionsupporting
confidence: 66%
“…Given these deficits, and the common view that the HD cell network contributes to the neural circuitry used for spatial navigation, the next logical question is whether our findings have identified a potential mechanism by which MK-801 causes spatial deficits. In support of this possibility, as presented in Table 3 many behavioral studies report spatial deficits following administration of MK801 at doses equal or greater than the dose at which our effects on the HD system were apparent (e.g., Butelman, 1989; Ward et al, 1990; Uekita & Okaichi, 2005). Even more convincing, some studies testing multiple doses of MK-801 have found spatial deficits at our high dose 0.1 mg/kg but no or reduced effects at our ineffective dose of .05 mg/kg (Filliat & Blanchet, 1995; Van der Staay et al, 2011;Whishaw & Auer, 1989).…”
Section: Discussionmentioning
confidence: 60%
“…Our findings, coupled with evi dence that disruption of the HD network is associated with spatial deficits (Aggleton, Hunt, Nagle, & Neave, 1996;Clark et al, 2013;van Groen, Kadish, & Wyss, 2002;Wilton, Baird, Muir, Honey, & Aggleton, 2001), provide a potential mechanism by which NMDA antagonism disrupts spatial behavior. It is notable that some stud ies have found that spatial learning is most impaired by NMDA blockade when the training occurs in an unfamiliar environment (Caramanos & Shapiro, 1994;Uekita & Okaichi, 2005), which is consistent with our findings and the premise that the acquisition of a spatial task is dependent on the consolidation of the novel environment into the neural circuitry supporting spatial behavior.…”
Section: Relationship Between Our Findings and Spatial Learning Deficsupporting
confidence: 92%
“…In fact, after considering the sensorimotor disturbances caused by MK-801, the impairment of learning almost vanished Saucier et al, 1996;Keith and Galizio, 1997). Moreover, other lines of studies support the idea that MK-801 does not impair the retrieval process (Heale and Harley, 1990;Venable and Kelly, 1990;Uekita and Okaichi, 2005). Most importantly, if there was any effect of MK-801 on memory retrieval, it seems impossible that MK-801 would just impair the retrieval of morphine-related memory, but spare the retrieval of food-related memory.…”
Section: Discussionmentioning
confidence: 87%